Amino Acids Metabolism in the Muscle of Sheep fed with Mitchell Grass Hay Supplemented with Gliricidia sepium - Y. Widiawati; M. Winugroho; E. Teleni (Atom Indonesia, 2018)
Leaf of Gliricidia sepiumcontains high amino acid that required for protein synthesis in the muscle. Supplementation of the legume leaves to low quality basal diet would improves amino acids amount to obtain an optimum growth of animal. The aim of experiment was to investigate the effect of Gliricidia sepium leaves supplementation to low quality basal diet on protein synthesis in muscle of animal. Eighteen sheeps were divided into three groups based on live weight (27.6 ± 1.72, 27.1 ± 2.26 and 27.5 ± 1.56 kg) of feed treatment, namely Mitchell grass hay (MG), Gliricidia (GS),and haycombined with Gliricidia (MGGS). All the dietwas offered with the amount was determined to meet the maintenance metabolizable energy (ME) requirement of the animals. Feed utilization and amino acid metabolism in muscle of sheep was measured with radioactively labeled leucine, water and sodium bicarbonate. Results indicated that sheepin MG group had a negative energy balance, whereas sheep in MGGS group had the highest amount of ME available for growth. The rate of protein synthesis was higher in the MGGS group and tended to take up these amino acids in their hind-limb muscles, while animalsin MG and GS groups tended to have net outputs of amino acids from their hind-limb muscles. Animals in the MGGS group synthesised more protein in their muscle than those in the GS and MG groups. It was concluded that the supplementation of Gliricidia at a ratio of 40:60improved feed utilization of low quality basal diet. The improvement would be manifested in better digestible organic matter intake (DOMI) with subsequent better utilization of amino acids.